The mediation as a way to resolve family disputes - Parneta, Oksana; Fedyk, Solomiia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2021)
The article highlights the essence and importance of mediation as an alternative way to resolve conflicts. The principles and stages of using the mediation procedure in resolving family disputes are considered. The advantages of family mediation are substantiated, as it allows to take into account the high emotionality of family misunderstandings, the human factor in the conflict and pays much attention to the relationship, and therefore helps the parties to resolve differences and cooperate voluntarily to make informed decisions. the lowest cost and confidentiality, which is certainly an extremely important aspect in dealing with family matters. Family mediation is used as a pre-trial, out-of-court means of resolving a family dispute, as well as in the process of court proceedings and at the stage of execution of a court decision. Family mediation also works with those categories of cases that cannot be the subject of a court dispute, intergenerational conflicts, interpersonal misunderstandings in the family, and some categories of inheritance cases. The role and principles of the mediator’s work in ensuring communication and making mutually beneficial decisions for the conflicting parties are substantiated, which contributes to comprehensive and effective conflict resolution, maintaining friendly relations, and reaching agreements that each party will voluntarily fulfill. The effectiveness of family mediation when working with children has been studied. The analysis of normative-legal regulation of mediation in Ukraine is carried out. The necessity of legal regulation and introduction of the mediation procedure as an alternative way of resolving family disputes is substantiated, which will provide a quick out-of-court settlement of the dispute, help unload the judicial system, provide opportunities to improve and simplify access to justice. Based on foreign experience, conclusions have been drawn on the expediency of proper legal support of the mediation procedure in Ukraine, which will bring the provisions of national justice closer to European standards.